The research Pengaruh Pupuk Organik Cair dari Kulit Kacang Tanah dan Kulit Pisang terhadap Pertumbuhan Vegetatif Bayam - Dyah Rini Indriyanti; Putut Marwoto; Retno Sri Iswari; Edy Cahyono; Rusdiyana Rusdiyana (Postgraduate, University of Mataram, 2022)
The liquid organic fertilizer (LOF) formula from peanut and banana peels. This research aims to: (1). Analyze the effect of LOF provision from peanut and banana peels on the vegetative growth of spinach; (2). Analyze the best LOF dose for vegetative growth of spinach, and (3). Analyze the effect differences between NPK fertilizer and LOF from peanut and banana peels toward the vegetative growth of spinach. The researchers promoted this study from November to December 2020 in a greenhouse in Banjarbaru. The researchers applied RAL design by providing fertilizer since the spinaches were 10, 17, and 24 days. The vegetative growth parameters were: Plant height, number of leaves, leaf width, and the leave color. The result proved that: (1). LOF provisions from peanut and banana peels significantly influenced the height and leave numbers of spinach; (2). The best dose for LOF provision is 50ml of peanut peel LOF + 50ml of banana peel LOF to get excellent height and leave numbers of the spinach; (3). The growth of the spinach, in terms of height, numbers of leaves, and leaf width during NPK fertilizer provision, was in line with the provisions of banana and peanut peel LOF.